2004
DOI: 10.1080/07399330490253193
|View full text |Cite
|
Sign up to set email alerts
|

Counseling About Contraception Among Repeated Aborters in Ho Chi Minh City, Vietnam

Abstract: We conducted qualitative interviews with 30 repeated abortion clients in Ho Chi Minh City, Vietnam. Only 5 women were practicing contraception regularly. A common reason for the nonusage of contraceptives was adverse health effects. Half of women were not counseled during the previous abortions, and contraceptives were given without explanation. Women pointed out that the current service was not enough or in-depth and was not meeting their needs. The type of counseling they wanted was a face-to-face discussion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2005
2005
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Many unmarried couples have consequently had limited access to services providing ongoing contraceptive provision, advice and monitoring. Moreover, a study by Xinh et al (2004) found that Vietnamese women were unsatisfied with the tertiary-level family planning services provided at the time of abortion. Counselling sessions were unfriendly and did not meet women's needs.…”
Section: Introductionmentioning
confidence: 96%
See 4 more Smart Citations
“…Many unmarried couples have consequently had limited access to services providing ongoing contraceptive provision, advice and monitoring. Moreover, a study by Xinh et al (2004) found that Vietnamese women were unsatisfied with the tertiary-level family planning services provided at the time of abortion. Counselling sessions were unfriendly and did not meet women's needs.…”
Section: Introductionmentioning
confidence: 96%
“…2 A significant proportion of youth abortions are repeat abortions, which has been a long-standing public health issue. About half of all abortion-seeking women and about one-quarter of unmarried abortion-seeking women have had at least one prior abortion (Belanger and Khuat 1998;Xinh et al 2004). While the total abortion rate fell from 2.5 per woman per lifetime in 1996 to 0.6 in 2002 (Sedgh et al 2007), current trends are unclear given incomplete statistics.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations